THE INFLUENCE OF ATTRACTION, PRICE PERCEPTION AND PROMOTION ON THE DECISION OF TOURISTS TO VISIT TAMAN SAFARI BOGOR - Ambar Pujiyani Jamaludin Putri; Ricky Talumantak (Human Capital Development, 2022)
This study aims to determine and analyze the influence of tourist attraction, price perception and promotion on tourist decisions to visit Taman Safari Bogor with a quantitative method, the data used is primary data by collecting data using questionnaires and using SPSS data processing to obtain the research population. are all visitors who have visited the Bogor Safari Park tourist attraction. The sample that will be taken by the author is 100 respondents with an accidental sampling technique. This research also uses multiple linear regression analysis approach. So from the results of this study, it is stated that the first and third variables partially have a positive and significant effect on Tourist Attractions and Promotions Decisions on Tourists Visiting Taman Safari Bogor, while the second variable partially Price Perceptions does not significantly affect the Decisions of Tourists Visiting Taman Safari Bogor. While the dependent or independent variables simultaneously affect the decision of tourists to visit the Bogor Safari Park.